THE ROLE OF SEGMENTATION IN MARKETING TARGET SETTING IN INTERNATIONAL LARGE B2B COMPANIES - Heikkilä, Janita Adele (My University, 2020)
ABSTRACT The increasing interest in the measurability of marketing opportunities and activities in global B2B companies has brought a question of how the measurability should proceed, especially in large organisations. Many companies base their marketing measurability in data-driven marketing activities. The data-driven marketing, even if being already widely used in consumer marketing, is still in the development state in many business-to-business organisations. It is essential to find out how the measurability can be conducted back to the activities, how the target setting should be done and where should it be sent. The role of segmentation is widely known in strategic business development, and hence this master’s thesis focuses on defining the role of segmentation in marketing target setting. The empirical data was gathered with semi-structured interviews with global, large B2B companies. Eight case companies were represented by marketing and sales professionals. The interviewees had all experience and are daily in operating with segments, marketing target setting and reporting. Based on the interviews, it was found that the companies use data-driven marketing approach in nearly all companies to make marketing activities more targeted and measurable. The segmentation is used in target setting and target group defining, but the results are reflected usually to the marketing activity instead of the segment. Despite this found, interviewees agreed that the target could be directed back to the segments if wanted to, but that was unnecessary as the segments were used in the early point of the process and prioritised, but were not present in the late activities, where the content played a more critical role. The segmentation was seen as a necessary tool to be developed, and an active part of strategic marketing in order to create profitability indirectly.
Keywords: segmentation; digital marketing; business-to-business marketing; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business